Evaluasi Penggunaan Flowgorithm dalam Pembelajaran Algoritma Pemrograman menggunakan Technology Acceptance Model (TAM) - Hisamuddin, Muhammad Zida; Siregar, Maria Ulfah (Universitas Hamzanwadi, 2024)
be able to automate work and software development. However, a programmer must understand the basics of computational thinking that often causes a problem for students who are desirous of becoming programmers. This extensive research aims to evaluate student's acceptance of the use of flow Flogorithm using the Technological Acceptance Model (TAM) method. This type of research is quantitative and is conducted by using a survey method which involves distributing questionnaires to around 96 respondents who have particularly studied programming algorithms. Furthermore, the random sampling technique was used in the sampling. The analysis was carried out using the PLS-SEM method which consists of a measurement model and structural model with five variables, namely ease of use, perceived usefulness, attitude towards use, intention, and actual use. The result of the research shows that the acceptance of the Flowgorithm has a positive influence on all the set of variables, except for the perceived ease of use on attitude toward using.